2015
DOI: 10.5539/gjhs.v8n7p260
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Students’ Self-Efficacy and Teachers’ Educational Leadership Style in Iranian Midwifery Students

Abstract: Background:Self-efficacy is believe in and feeling of ability to complete work. One of these factors is educational teachers’ role. This study aimed to determine relationship between teachers’ leadership style and students’ self-efficacy in midwifery students.Method:This Study is a cross sectional correlation study. Sampling was conducted in midwifery students in Bachelor Science degree in 2013. Data collection tools were multi leadership questionnaire and self-efficacy clinical performance. After explaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
6
0
1
Order By: Relevance
“…A predominance of moderate to high self-efficacy was observed in the sample, with a mean score of 35.29, corroborating findings from other international studies that also showed a predominance of moderate self-efficacy in this same population. 18,[21][22] The results showed that male individuals presented higher self-efficacy compared to the female gender. The literature also indicates a higher level of self-efficacy in men, relating this fact to higher scores of perceived stress, psychological distress, somatic and anxious symptoms present in women.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A predominance of moderate to high self-efficacy was observed in the sample, with a mean score of 35.29, corroborating findings from other international studies that also showed a predominance of moderate self-efficacy in this same population. 18,[21][22] The results showed that male individuals presented higher self-efficacy compared to the female gender. The literature also indicates a higher level of self-efficacy in men, relating this fact to higher scores of perceived stress, psychological distress, somatic and anxious symptoms present in women.…”
Section: Discussionmentioning
confidence: 96%
“…This association was observed mainly in the transformational leadership style, whose pillars are based on trust, respect, collaboration and commitment, characteristics that favored greater self-efficacy in the students. 22 To better understand the behavior of this variable and the teacher's role in this context, a longitudinal study conducted in the United Kingdom presented an adaptation curve experienced by the students throughout their undergraduate studies. Between the first and fourth months of this period, there were increased levels of anxiety and uncertainty related to the transition process and necessary adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for an in-depth review of ethical considerations to justify difficult decisions and protect us against those lacking ethical backgrounds ( 12 - 13 ). Ethical problems arise in various areas of a pandemic such as restrictions on moving around freely, individuals’ refusal to adhere to preventive intervention, rights and duties of the healthcare workers, allocating limited resources, and off-label use of diagnostic and therapeutic measures ( 14 - 15 ). During the critical time of the COVID-19 pandemic, it has been crucial for the academic community to learn from this experience and prioritize a prospective and scholarly approach by implementing practical strategies ( 15 - 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interações pautadas no acolhimento, cooperação, respeito e confiança são capazes de influenciar positivamente esse constructo nesses indivíduos. (28) Mediante estes resultados, é recomendável que as IES, por meio de programas preventivos, auxiliem o desenvolvimento emocional e acadêmico de seus alunos, com ações de promoção a saúde mental, identificação precoce de emoções negativas e oferecimento de apoio psicológico aos estudantes vulneráveis, (3) sobretudo àqueles no início do curso.…”
Section: Discussionunclassified